The Relationship Between Educational Factors and Early Detection Behavior Cervical Ca in Fertile Age Women - Darwati, Lilik; Nikmah, Khusnul (STRADA : Jurnal Ilmiah Kesehatan, 2020)
From the results of the study, it is known that almost half of the respondents in the implementation of cervical caesarean education, including less, namely 13 0 respondents and most of the respondents carried out early detection of cervical caverns with Pap smear, as many as 272 respondents out of a total of 369 respondents. There is a relationship between educational factors and the behavior of early detection of cervical caesarean at WUS p value 0.000 <0.05. Education is necessary in order untu k make someone knows d an encouraging someone to carry out early detection of ca cervix. There is a relationship between educational factors on the behavior of early detection of cervical cancer in women of childbearing age because the realization of behavior requires a variety of factors as a predisposition for the realization of behavior